Cultura política e democracia : apoio difuso e específico entre um segmento da elite não estatal do município de Maringá (PR) - Gimenes, Éder Rodrigo (2011)
The Brazil is currently in the second period of democratic transition after the authoritarian experience occurred in the past century. The new regime has shown positive signs of development, experiencing other forms of participation other than voting, such as participatory budgets, public hearings, management councils and plebiscites, for example. Despite this, authors as Moisés (1995, 2005), Lima and Cheibub (1996) and Ribeiro (2008, 2011) identified in their research different levels of adherence to democratic regime in Brazil, with distinction between support for democracy in the abstract and evaluative measures, as defined by Easton (1975). In general, these researchers have found that the incorporation of abstract values pro-democracy have spread between the national society, while the evaluations on their performance concrete has been shown to be negative. If the existence of this incongruity between the general population can be interpreted as a factor of political instability in the medium and long term, we assume that the effects are even more relevant when there is between what we might call the political elites. In this sense, this research aims to verify the existence of this gap between diffuse support and specific support for democracy among individuals belonging to an non-state segment of elite of Maringá (PR), with a view to understanding their values about scheme and the identification of agreement or disagreement with respect to sample national, regional and local about this incongruity. To do so, survey type questionnaire was administered to a representative sample of heads of associations and private foundations nonprofit legally established in the municipality, which holds certificate of recognition by the Federal Government. The results found showed a strong abstract support to democracy and intermediate measures of specific support, demonstrating that this segment of the elite non-state has a political culture that does not differ from the Brazilian population in general about the gap between the two levels of membership.